A Case of Anorexia Nervosa with Focal Cortical Dysplasia - Hiroki Nemoto; Kazuo Imagawa; Takashi Enokizono; Yosuke Masuda; Masayuki Ide; Takuma Deguchi; Monami Hara; Atsushi Morita; Takahiro Kido; Mai Tanaka; Tatsuyuki Ohto; Hidetoshi Takada (Case Reports in Psychiatry)
Anorexia nervosa (AN) is a fatal condition associated with extreme underweight and undernutrition. It is more common in young females, with a female-to-male ratio of 10 : 1. Focal cortical dysplasia (FCD) is characterized by dysplasia of the cerebral cortex and is a common cause of pharmacoresistant epilepsy. However, FCD associated with AN has never been reported. We report the first case of AN in a 12-year-old male diagnosed with FCD-type 2 on head magnetic resonance imaging (MRI). He became concerned about lower abdominal distention and began reducing his food intake. He was admitted to our hospital after weight loss of 10 kg in a 1 year. Head MRI showed a localized high-signal area from the cortex to the white matter of the fusiform gyrus near the left hippocampus, with no associated decreased blood flow or electroencephalography (EEG) abnormalities. These findings were characteristic of FCD type II. In males with AN, the search for underlying disease is particularly important. The pathophysiology of the association between AN and FCD is unclear. However, both conditions are reportedly associated with autism spectrum disorder. Further cases are needed to clarify whether FCD is associated with eating disorders.